2018
DOI: 10.1016/j.clinthera.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Role of Physical Activity and Exercise in Alleviating Cognitive Impairment in People With Epilepsy

Abstract: Many persons with epilepsy (PWE) experience problems with a wide range of cognitive functions, including learning, memory, attention, and executive control. These deficits in cognition result in diminished quality of life for PWE and are related to many factors, including the etiology of their epilepsy, recurrent seizures, side effects of antiseizure medications, or a combination of these factors. Various treatments to ameliorate cognitive deficits experienced by PWE have been implemented, although noninvasive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 78 publications
0
24
0
Order By: Relevance
“…Moreover, HMGB1 has been implicated in memory impairment by mediating the effects of RAGE and TLR4 (Mazarati et al 2011). An earlier study alarmingly revealed that one half of PWE exhibit cognitive dysfunctions (Jensen 2011) in one or more domains, including learning, memory, attention, and executive functioning, though memory impairment is the most common (Allendorfer and Arida 2018). Currently, there is no anti-seizure drugs available with dual effects that can retard seizure frequency as well as improve associated cognitive dysfunction.…”
Section: Future Perspective Of Hmgb1mentioning
confidence: 99%
“…Moreover, HMGB1 has been implicated in memory impairment by mediating the effects of RAGE and TLR4 (Mazarati et al 2011). An earlier study alarmingly revealed that one half of PWE exhibit cognitive dysfunctions (Jensen 2011) in one or more domains, including learning, memory, attention, and executive functioning, though memory impairment is the most common (Allendorfer and Arida 2018). Currently, there is no anti-seizure drugs available with dual effects that can retard seizure frequency as well as improve associated cognitive dysfunction.…”
Section: Future Perspective Of Hmgb1mentioning
confidence: 99%
“…In general, fewer people with epilepsy show physical activity at the recommended level [44]. Importantly, other studies address the potentially bene cial role of physical activity in improving the cognitive function of patients with epilepsy [73] and quality of life [74]. Scienti c evidence indicates that it is reasonable to educate patients with epilepsy about their lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, to date, few studies have examined the effect of physical exercise on cognitive function in adults with epilepsy 13,15 . Strategies to reduce the burden of common adverse effects such as cognitive impairment in people with epilepsy must be developed 3,16,17 . Thus, this study aimed to examine the effect of a 12‐week exercise program on cognitive function in people with epilepsy.…”
Section: Introductionmentioning
confidence: 99%